Visualizing Chemistry: The Progress and Promise of Advanced Chemical Imaging - National Research Council (The National Academies Press, 2006)
Scientists and engineers have long relied on the power of imaging techniques to help see objects invisible to the naked eye, and thus, to advance scientific knowledge. These experts are constantly pushing the limits of technology in pursuit of chemical imaging—the ability to visualize molecular structures and chemical composition in time and space as actual events unfold—from the smallest dimension of a biological system to the widest expanse of a distant galaxy. Chemical imaging has a variety of applications for almost every facet of our daily lives, ranging from medical diagnosis and treatment to the study and design of material properties in new products. In addition to highlighting advances in chemical imaging that could have the greatest impact on critical problems in science and technology, Visualizing Chemistry reviews the current state of chemical imaging technology, identifies promising future developments and their applications, and suggests a research and educational agenda to enable breakthrough improvements.
Keywords: Math, Chemistry, and Physics; Surveys and Statistics

From Maps to Models: Augmenting the Nation's Geospatial Intelligence Capabilities - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
The United States faces numerous, varied, and evolving threats to national security, including terrorism, scarcity and disruption of food and water supplies, extreme weather events, and regional conflicts around the world. Effectively managing these threats requires intelligence that not only assesses what is happening now, but that also anticipates potential future threats. The National Geospatial-Intelligence Agency (NGA) is responsible for providing geospatial intelligence on other countries—assessing where exactly something is, what it is, and why it is important—in support of national security, disaster response, and humanitarian assistance. NGA's approach today relies heavily on imagery analysis and mapping, which provide an assessment of current and past conditions. However, augmenting that approach with a strong modeling capability would enable NGA to also anticipate and explore future outcomes.
Keywords: Earth Sciences; Math, Chemistry, and Physics; Surveys and Statistics

Reproducibility and Replicability in Science - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
One of the pathways by which the scientific community confirms the validity of a new scientific discovery is by repeating the research that produced it. When a scientific effort fails to independently confirm the computations or results of a previous study, some fear that it may be a symptom of a lack of rigor in science, while others argue that such an observed inconsistency can be an important precursor to new discovery. Concerns about reproducibility and replicability have been expressed in both scientific and popular media. As these concerns came to light, Congress requested that the National Academies of Sciences, Engineering, and Medicine conduct a study to assess the extent of issues related to reproducibility and replicability and to offer recommendations for improving rigor and transparency in scientific research. Reproducibility and Replicability in Science defines reproducibility and replicability and examines the factors that may lead to non-reproducibility and non-replicability in research. Unlike the typical expectation of reproducibility between two computations, expectations about replicability are more nuanced, and in some cases a lack of replicability can aid the process of scientific discovery. This report provides recommendations to researchers, academic institutions, journals, and funders on steps they can take to improve reproducibility and replicability in science.
Keywords: Surveys and Statistics; Policy for Science and Technology

A Smarter National Surveillance System for Occupational Safety and Health in the 21st Century - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2018)
The workplace is where 156 million working adults in the United States spend many waking hours, and it has a profound influence on health and well-being. Although some occupations and work-related activities are more hazardous than others and face higher rates of injuries, illness, disease, and fatalities, workers in all occupations face some form of work-related safety and health concerns. Understanding those risks to prevent injury, illness, or even fatal incidents is an important function of society.
Keywords: Health and Medicine; Behavioral and Social Sciences; Industry and Labor; Surveys and Statistics